PS09 Sleep Problems: An Emerging Global Epidemic? Findings from the Indepth Who-Sage Study among over 40, 000 Older Adults from Eight Countries Across Africa and Asia. (17th September 2012) - Stranges, S; Tigbe, W; Gómez-Olivé, FX; Thorogood, M; Kandala, N-B
Abstract : Background: Several studies have reported downward trends in the average duration of sleep and an increasingly higher prevalence of sleep problems across different Western populations. However, the evidence from low-income countries is limited. This study aims to fill this gap by examining the prevalence of sleep problems and associated factors in low-income settings. Methods: Community-wide samples were taken from eight countries across Africa and Asia participating in the INDEPTH WHO-SAGE multicentre collaboration during 2006–2007. The participating sites included rural populations in Ghana, Tanzania, South Africa, India, Bangladesh, Vietnam and Indonesia, and an urban area in Kenya. The overall sample comprised 24, 434 women and 19, 501 men, for a total of 43, 935 participants, aged 50 years and over. Two measures of sleep quality, over the last 30 days, were assessed alongside a number of socio-demographic variables, measures of quality of life, and co-morbidities. Results: Overall 16.6% of participants reported severe/extreme nocturnal sleep problems, with a striking variation across the eight populations, ranging from 3.9% (Purworejo, Indonesia, and Nairobi, Kenya) to over 40.0% (Matlab, Bangladesh). There was a consistent pattern of higher prevalence of sleep problems in women and older age groups. In bivariate analyses, lower education, not living in partnership, and poorer self-rated quality of life were consistently associated with higher prevalence of sleep problems (P<0.001). In multivariate logistic regression analyses, limited physical functionality or greater disability and feelings of depression and anxiety were consistently strong, independent correlates of sleep problems, both in women and men, across the eight sites (P<0.001). Conclusion: A large number of older adults in low-income settings are currently experiencing sleep problems, which emphasises the global dimension of this emerging public health issue. This study corroborates the multifaceted nature of sleep problems, which are strongly linked to poorer general wellbeing and quality of life, and psychiatric co-morbidities.